The Dynamics of Persuasion - Richard M. Perloff (Taylor & Francis, 2010)
PERSUASION is such an endemic feature of American society that new exemplarsâ€” communicators, messages, and campaignsâ€”emerge constantly. Just as the third edition was hitting academic bookstores, Americans found themselves in the midst of an electrifying election campaign. How could a persuasion book not touch on some of the path-breaking dimensions of the 2008 campaign? But youâ€™ve just written a third edition, I told myself; isnâ€™t it a little soon? As I mulled over this question, I came across more applications: jazzy examples of product placements in entertainment programming, health campaigns migrating to the Web, unsavory mortgage companies devising persuasion ploys to manipulate home buyers, and new insights on coercion and persuasion at the Abu Ghraib prison camp in Iraq. At the same time, new research on attitudes and persuasion continued apace. A social psychologist replicated the Milgram study! Communication scholars published interesting studies of fear-arousing messages, guilt appeals, and health campaigns. There was just enough new to refurbish the old. Why wait? With new research on the 2008 election campaign and time-honored ethical issues emerging in new contexts, there was more than enough to justify the arduous, but glorious, process of cutting and pasting, rewriting and revising. A fourth edition was hatched. Two changes stand out, in my view. The first is the addition of political persuasion examples, chiefly from the 2008 campaign, capped off by a boxed section on negative advertising in Chapter 11. I try to show how persuasion theories help us understand campaign persuasion and strive to be scrupulously fair to all sides. Second, I have long recognized that the narrative a writer threads in a scholarly textbook leaves the impression that questions have been answered and knowledge, alas, has been obtained. But knowledge is not fixed and static, but changing. Just as a book tells you what we know, it should also tell you what we do not know or understand. In the final chapter I have added a boxed section that discusses what we do not know about persuasion and need to comprehend. The book has plenty of new applications, with dozens of new citations of research. Chapter 1 features a definition of manipulation and an updated discussion of persuasion and coercion in cults. The Iraq war example that showcased attitudes in Chapter 2 has become dated. In its place is an example of a less political, but no less contentious, issue: animal research. Chapters 3 and 4 include new citations and research. The fifth and sixth chapters include updates of research on processing and sources (including the Milgram replication in Chapter 6), as well as contemporary applications of theory to context. Chapter 7 offers a new section on guilt appeals, in-depth discussion of gain and loss effects on fear appeals, and a box on the ethics of marketing a cervical cancer vaccine. The eighth and ninth chapters are largely unchanged, save new research and examples, such as a memorable application of dissonance theory early in the chapter. Chapter 10 includes a boxed section that shows how compliance-gaining can be applied to critical communications between airline pilots. Chapter 11 contains a variety of up dates, showcasing the changing world of advertising, as well as a box on negative advertising. The final chapter offers more discussion of the Web campaign context, with examples and methodological caveats. It also includes new discussions of psychological reactance, campaigns to reduce racial disparities in health care, and the box entitled, â€œWhat we do not know about persuasion.â€